The Role of Monocytes in Ischemic Stroke Pathobiology: New Avenues to Explore - ElAli, Ayman; Jean LeBlanc, Noëmie (Frontiers in Aging Neuroscience, 2016)
Ischemic stroke accounts for the majority of stroke cases and constitutes a major cause of death and disability in the industrialized world. Inflammation has been reported to constitute a major component of ischemic stroke pathobiology. In the acute phase of ischemic stroke, microglia, the resident macrophages of the brain, are activated, followed by several infiltration waves of different circulating immune cells into the brain. Among these circulating immune cells, monocytes have been shown to play a particularly important role. Following their infiltration, monocytes differentiate into potent phagocytic cells, monocyte-derived macrophages (MDMs) in the ischemic brain. Initially, the presence of these cells was considered as marker of an exacerbated inflammatory response that contributes to brain damage. However, the recent reports are suggesting a more complex and multiphasic roles of these cells in ischemic stroke pathobiology. Monocytes constitute a heterogeneous group of cells, which comprises two major subsets in rodent and three major subsets in human. In both species, two equivalent subsets exist, the pro-inflammatory subset and the anti-inflammatory subset. Recent data have demonstrated that ischemic stroke differentially regulate monocyte subsets, which directly affect ischemic stroke pathobiology and may have direct implications in ischemic stroke therapies. Here we review the recent findings that addressed the role of different monocyte subsets in ischemic stroke pathobiology, and the implications on therapies.